2021
DOI: 10.1002/jmv.27145
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity assay for detection of SARS‐CoV‐2 in samples from patients with COVID‐19

Abstract: Since the coronavirus disease 2019 (COVID‐19) outbreak, laboratory diagnosis has mainly been conducted using reverse‐transcription polymerase chain reaction (RT‐PCR). Detecting the presence of an infectious virus in the collected sample is essential to analyze if a person can transmit infectious severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). However, there have been no quantitative investigations conducted for infectious SARS‐CoV‐2 in clinical samples. Therefore, in the present study, a rapid an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 39 publications
(117 reference statements)
1
22
1
Order By: Relevance
“…Viral titer in the upper respiratory tract-derived body fluid of patients infected with IAV and SARS-CoV-2 ranged from 1.0 × ×10 2 to 2.0 × ×10 6 FFUs/mL or TCID 50 /mL [ [16] , [17] , [18] , [19] ]. When 10–100 μL of the infectious body fluid is deposited on a paper surface, the maximum absolute viral titer on the paper surface is approximately 2.0 × ×10 5 FFUs or TCID 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Viral titer in the upper respiratory tract-derived body fluid of patients infected with IAV and SARS-CoV-2 ranged from 1.0 × ×10 2 to 2.0 × ×10 6 FFUs/mL or TCID 50 /mL [ [16] , [17] , [18] , [19] ]. When 10–100 μL of the infectious body fluid is deposited on a paper surface, the maximum absolute viral titer on the paper surface is approximately 2.0 × ×10 5 FFUs or TCID 50 .…”
Section: Discussionmentioning
confidence: 99%
“…A negative correlation between age and the antiviral activity of IFN-based therapies was observed in previous studies. Honda et al evaluated the efficacy of combination therapy with peginterferon-alfa-2b and ribavirin in patients with chronic HCV infection [ 23 ]. The study showed that sustained viral response (SVR) rate was lower in elderly patients (≥ 65 years) than in younger patients (< 65 years).…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome was to compare the median time from the date of the last SARS-CoV-2 RT-PCR positive examination to the date of the first RT-PCR negative conversion and patient overall RT-PCR negative conversion time between the ropeginterferon alfa-2b and SOC alone groups. SARS-CoV-2 RT-PCR negative conversion was defined as the first detection of C t value ≥ 30 after treatments [ 21 – 23 ]. Safety was evaluated by the occurrences of AEs and SAEs after receiving the single dose of ropeginterferon alfa-2b.…”
Section: Methodsmentioning
confidence: 99%
“…SARS-CoV-2 (JPN-TY-WK-521) was obtained from the National Institute for Infectious Diseases, Japan. Clinical isolates hCoV-19/Japan/OIPH14/2020 and hCoV-19/Japan/OIPH21/2020 57 were propagated in TMPRSS2/VeroE6 cells 58 that were obtained from the National Institutes of Biomedical Innovation, Health and Nutrition, Japanese Collection of Research Bioresources Cell Bank, Japan. K-ML2 cells were established as described previously 59 and maintained in minimum essential medium supplemented with 10% fetal calf serum.…”
Section: Viruses and Cellsmentioning
confidence: 99%